Retention of Platelets by Glass Beads Variation with the Age of the Individual - Bucher, U; Robert, Y; Riedwyl, H (Thrombosis and Haemostasis, 1973)
Platelet function has been evaluated by Hellem’s original method in carefully screened normal persons of various ages. Factors which could possibly influence platelet behaviour, such as drugs, smoking, hypercholesteremia, prediabetes, hypertension or uremia were excluded in preliminary examinations. Only individuals in perfect health without a history of coronary heart disease, peripheral vascular disease or other thrombotic disorders were selected. Physical activity did correspond to the age. Variation in results possibly due to technical factors were eliminated by using strictly the same method and material throughout the study and by performing the tests within a relatively short period of time. From an original group of 109 normal persons, 70 individuals between the ages of 10 and 90, who corresponded to the described standards were chosen for further trials. They were divided into 7 age groups, each including 10 individuals within a decade (the last group ranging from 70 to 90 years). Retention of platelets in a column of glass beads was measured by Hellem5s method. The results, expressed as per cent retention and represented graphically, form a parabolic curve with its minimum at the age of 35 (mean ± 2 SD = 50 i 22%). The mathematical function of the curve can be expressed in a formula as second degree polynomial. It is shown by analysis of variance that age is the only factor on which the slope of the curve depends. Physiological or pathological implications of these findings are not known. The results, however, show that age must be taken into account when differences of platelet behaviour are discussed.